FREQUENCY OF FAMILIAL OCCURRENCE AND ASSOCIATED AUTOIMMUNE DISEASES IN A COHORT OF PATIENTS WITH ACQUIRED AUTOIMMUNE MYASTHENIA GRAVIS FROM BELGRADE - Josipović, Maša B; Jovanović, Aleksa Lj; Jadžić, Jelena; Jovanović, Jovan; Lavrnić, Dragana (Medicinski podmladak, 2017)
Introduction: Myasthenia gravis (MG) can be associated with other autoimmune diseases (AID), most frequently with Hashimoto’s thyroiditis, systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Familial occurrence (FOMG) is rare and it exists in 3.5-4.2% patients with MG. Aim: To determine the occurrence of FOMG, the occurrence of AID associated with MG and to identify potential risk factors for developing MG in a cohort of patients from Belgrade. Material and Methods: This study gathered data from 453 patient histories from the period 1992-2014 from the Clinic of Neurology, Clinical Center of Serbia. Three analyses were performed. The first measured the frequency of associated AID in patients with MG. In the second, patients who had MG associated with AID were compared to patients without associated AID. The third one included patients with FOMG  and compared them with patients without FOMG. The demographic and clinical characteristics of these patients were analysed and comparisons were made between observed and control groups. Results: The associated AID were present in 54 (11.9%) patients, the most frequent was Hashimoto thyreoiditis (4%), then SLE (1.3%), and RA, polymyositis and pernicious anaemia (0.9%). Patients with co-occurrence of MG and other AID were, in comparison with control group, more often female and the difference was on the border of statistical significance (p=0.056). They had late onset MG (LOMG) more frequently, a mild form of MG and positive anti-AChR antibodies, but these differences weren't statistically significant. FOMG was seen in 2.2% of patients. They had LOMG more frequently, were predominantly men, seropositive, and with mild form of the disease, but with no statistical significance compared to the control group. Conclusion: In the Belgrade cohort, MG was often associated with other AID, while FOMG was relatively rare. There was no statistically significant difference in the observed clinical and demographic characteristics of analysed groups compared to control groups. Key words: myasthenia gravis, familial occurrence, autoimmune diseases